The Training Curriculum Formulation on Prevention and Control of Dengue Haemorrhagic Fever and Avian Influenza for Village Health Volunteers in Suphan Buri Province - Pansri, Khumnuan; Suteeprasert, Tanin (Journal of Health Science of Thailand, 2018)
The objective of this quasi-experimental research was to formulate and implement the training curriculum on prevention and control of dengue haemorrhagic fever and avian influenza for village health volunteers (VHVs). The study was conducted in 3 steps; preparation of training curriculum, training curriculum formulation and implementation process and program evaluation on 8-9 May 2007. Samples were 60 VHVs, divided into 2 groups, an experimental group and a control group. The experimental group received 2 day training. The program evaluation was evaluated by questionnaires on knowledge, attitude, behaviors and satisfaction of training. Statistics used for data analysis were descriptive statistics: percentage, mean, and inference statistics: t-test and paired ttest. The finding of this study showed that before the experiment, the mean scores on knowledge,attitude and behaviors on dengue haemorrhagic fever and avian influenza of the experimental and control groups were not significantly different (p > 0.05). After the experiment, the mean scores on knowledge, attitude and preventive behaviors of the experimental group increased with statistical difference (p < 0.001), while those of the control group were not significantly different. The trainees were satisfied with the training curriculum formulation.